SLEEP DURATION, ANTHROPOMETRIC MEASUREMENTS AND METABOLIC SYNDROME IN OVERWEIGHT/OBESE ADOLESCENTS - Iitdrie; Widjaja, Nur Aisiyah; Hanindita, Meta Herdiana; Irawan, Roedi; Alexander, Yoppi Yeremia; Keya, Rino Tryanto; Hermanto, Edi; Ardianah, Eva; Qomaruddin, Mochammad Bagus; Muthmainnah, Muthmainnah; Noviyanti, Tausyiah Rohmah (Universitas Airlangga, 2025)
Introduction: Adolescents have sleep problems, as their sleep duration does not meet the recommended sleep duration of 8-10 hours, leading to various sleep-related problems. Sleep duration is suspected to have detrimental effects on health, such as non-communicable diseases including obesity, cardiovascular disease (CVD), and type 2 diabetes mellitus (T2DM). However, the correlation between sleep duration and the prevalence of obesity and metabolic syndrome (MetS) is still conflicting, especially in the adolescent population. This study aimed to examine and analyze the effect of sleep duration on anthropometric measurements and MetS in overweight/obese adolescents. Methods: A cross-sectional study involving healthy overweight/obese adolescents was conducted from September to October 2019 to evaluate the effect of sleep duration on anthropometric measurements, lipid profiles, fasting blood glucose levels, and blood pressure in overweight/obese adolescents. Results and discussion: A total of 197 subjects showed no significant differences in body height, BMI, waist circumference, blood pressure, and lipid profile based on sleep duration categories. Subjects with short sleepers were older than those with sufficient sleep (p<0.05). However, long sleepers were heavier, had larger BMI-for-age z-scores, and larger waist circumferences than sufficient and short sleepers (p<0.05). However, the differences between the short, sufficient, and long sleepers were U-shaped. Sleep duration was not correlated with MetS or MetS components (abdominal obesity, hyperglycemia, hypertriglyceridemia, hypertension, and low HDL-c). Conclusion: Long sleepers (>11 h/night) were heavier, had greater BMI-for-age z-scores, and larger waist circumference than (<sufficient sleeper (6-10 h/night), or short sleepers 6 h/night).